Analysis of the prognostic value of BMI and the difference in its impact according to age and sex in DLBCL patients. Issue 1 (27th April 2017) - Kanemasa, Yusuke; Shimoyama, Tatsu; Sasaki, Yuki; Tamura, Miho; Sawada, Takeshi; Omuro, Yasushi; Hishima, Tsunekazu; Maeda, Yoshiharu
Abstract: Studies that have evaluated the prognostic value of body mass index (BMI) in patients with diffuse large B‐cell lymphoma have recently been reported. However, the impact of BMI on survival outcomes remains controversial. We retrospectively analyzed the data of 406 diffuse large B‐cell lymphoma patients treated with R‐CHOP or R‐CHOP–like regimens. The number (%) of patients that were categorized into 1 of 4 groups according to BMI were underweight (<18.5 kg/m 2 ), 58 (14.3%); normal weight (≥18.5 to <25 kg/m 2 ), 262 (64.5%); overweight (≥25 to <30 kg/m 2 ), 75 (18.5%); and obese (≥30.0 kg/m 2 ), 11 (2.7%). While the prognosis of overweight patients was good, being similar to that of normal weight, underweight, and obese patients had a worse prognosis (5‐y overall survival [OS] was 57.9%, 74.3%, 73.4%, and 40.9% for underweight, normal weight, overweight, and obese patients, respectively; P = .004). In multivariate analysis, underweight and obesity were independent prognostic factors for OS compared with normal weight (hazard ratios 2.90 and 5.17, respectively). In elderly female patients (≥70 y), patients with a low BMI (<25 kg/m 2 ) had significantly inferior OS than those with a high BMI (≥25 kg/m 2 ) (5‐y OS, 61.5% vs 85.7%; P = .039). In contrast, in young female patients (<70 years), patients with a low BMI had significantly better OS than those with a high BMI (5‐y OS, 88.6% vs 46.4%; P < .001). In male patients, there were no differences in the effect of BMI on OS between young and elderly patients. In this study, we demonstrated that being underweight and obese were independent prognostic factors compared with being normal weight. In female patients, BMI had a different impact on the prognosis of young and elderly patients, whereas in male patients, there was no difference in the effect of BMI on prognosis according to age.